Pengembangan metodologi pembelajaran Islam berbasis nilai dan karakter - Supriatna, Dede; Mujahidin, Endin; Lisnawati, Santi (TAWAZUN: Jurnal Pendidikan Islam, 2025)
Islamic education plays a crucial role in shaping a generation that is not only intellectually intelligent but also morally and spiritually upright. However, the dominance of cognitive-oriented approaches in Islamic Religious Education (PAI) often creates a gap between knowledge acquisition and value internalization in students’ daily lives. This study aims to explore strategies for developing Islamic learning methodologies based on values and character, focusing on curriculum integration, religious habituation, contextual projects, and comprehensive character evaluation. This research employed a qualitative-descriptive method with a library research approach, complemented by field data from observation and documentation. The findings reveal that value-based learning enhances students’ affective engagement, strengthens religious practices, and fosters social responsibility. These results highlight the urgency of adopting holistic, integrative, and adaptive Islamic education methodologies in response to contemporary challenges. The study implies that strong collaboration among educators, schools, and policymakers is necessary to position Islamic education as an effective tool for character building.